The Home Environment and Asian Immigrant Children's Early Literacy Skills. (3rd April 2017) - Xu, Yiyuan; Farver, Jo Ann M.; Krieg, Alexander
SYNOPSIS: Objective. The current study examines how aspects of the home literacy environment were related to Asian immigrant children's early literacy skills. Design. One hundred and thirty-nine Asian immigrant families and their children (69 girls; mean age = 62.93 months; standard deviation   = 3.82) were recruited from kindergarten classrooms at seven public elementary schools in Honolulu, Hawaiʻi. Trained research assistants assessed children's early literacy skills in English at the beginning (T1) and end of kindergarten (T2). Parents (16% fathers; 84% mothers) rated their involvement in literacy-related activities in English and in their native language at T1, and classroom teachers rated children's interest in literacy at T2. Results. Our results showed that parents' literacy activities in English at T1 were positively related to children's English literacy skills at T1. Parents' literacy activities in English and in their native language at T1 were both related to children's interest in literacy at T2, which in turn was associated with children's English oral language skills at T2. Conclusion. These findings highlight the importance of examining the languages immigrant parents use during literacy-related activities.